Melanocyte Colonization and Pigmentation of Breast Carcinoma: Pathological and Clinical Aspects. (20th December 2012) - Mele, Marco; Laurberg, Tinne; Engberg Damsgaard, Tine; Funder, Jonas; Jensen, Vibeke
Abstract : Introduction . Melanocyte colonization of breast carcinoma by nonneoplastic melanocytes of epidermal origin is a rare and serious condition first described in 1977. We report on the exceptional clinical and pathological features of this migration phenomenon in a 74-year-old patient. Discussion . The pathogenesis by which melanocyte migration takes place is not known, but a breached basement membrane is considered essential. Conclusion . Histological examination and additional staining of skin are essential to differentiate breast cancer melanosis from malignant melanoma.